Rationale and design of a proof-of-concept trial investigating the effect of uninterrupted perioperative (par)enteral nutrition on amino acid profile, cardiomyocytes structure, and cardiac perfusion and metabolism of patients undergoing coronary artery bypass grafting - Cocchieri Riccardo; van Venrooij Lenny MW; Niessen Hans WM; Kok Wouter EM; Verberne Hein J; Davids Mariska; Visser Marlieke; Wisselink Willem; de Mol Bas AJM; van Leeuwen Paul AM (Journal of Cardiothoracic Surgery, 2011)
Abstract Background Malnutrition is very common in patients undergoing cardiac surgery. Malnutrition can change myocardial substrate utilization which can induce adverse effects on myocardial metabolism and function. We aim to investigate the hypothesis that there is a disturbed amino acids profile in the cardiac surgical patient which can be normalized by (par)enteral nutrition before, during and after surgery, subsequently improving cardiomyocyte structure, cardiac perfusion and glucose metabolism. Methods/Design This randomized controlled intervention study investigates the effect of uninterrupted perioperative (par)enteral nutrition on cardiac function in 48 patients undergoing coronary artery bypass grafting. Patients are given enteral nutrition (n = 16) or parenteral nutrition (n = 16), at least two days before, during, and two days after coronary artery bypass grafting, or are treated according to the standard guidelines (control) (n = 16). We will illustrate the effect of (par)enteral nutrition on differences in concentrations of amino acids and asymmetric dimethylarginine and in activity of dimethylarginine dimethylaminohydrolase and arginase in cardiac tissue and blood plasma. In addition, cardiomyocyte structure by histological, immuno-histochemical and ultrastructural analysis will be compared between the (par)enteral and control group. Furthermore, differences in cardiac perfusion and global left ventricular function and glucose metabolism, and their changes after coronary artery bypass grafting are evaluated by electrocardiography-gated myocardial perfusion scintigraphy and 18F-fluorodeoxy-glucose positron emission tomography respectively. Finally, fat free mass is measured before and after intervention with bioelectrical impedance spectrometry in order to evaluate nutritional status. Trial registration Netherlands Trial Register (NTR): NTR2183